Analisa Bauran Pemasaran Jasa Hotel Belangi Syariah Takengon - Diana, Rahma; Rizka, Irham (Jurnal Ilmiah Ilmu Manajemen, 2024)
This thesis is the result of research and discussion. The problem identification in this research is what is the marketing mix for the services of the Takengon Belangi Syariah Hotel. And the aim of this research is to determine the service marketing mix at the Belangi Syariah Takengon Hotel. And the benefit of this research is to develop good knowledge and apply the knowledge that has been obtained during the course. Information and references for the Belangi Syariah Takengon Hotel as well as a wealth of knowledge. The scope of this research concerns the analysis of the marketing mix of services at the Belangi Syariah Takengon Hotel. The respondents for this research were the managers and employees of the Belangi Syariah Takengon Hotel, totaling 5 people. This data collection was carried out by observation and interviews. The research results show that in terms of product, the main product of the Belangi Syariah Takengon Hotel is rooms with 5 types, namely family rooms, deluxe rooms, twin rooms, standard double rooms and single rooms. For price, in determining the price of the Belangi Syariah Takengon Hotel, it refers to the facilities, the price is according to its class, namely IDR 300,000 for a single room, standard double room type IDR. 365,000, twin room type Rp. 550,000, deluxe room type Rp. 665,000, and family room for Rp. 800,000. For Place, the location of the Hotel Belangi Syariah Takengon is strategic and very easy to access for consumers who come from outside Takengon. For People, employees provide good, fast, friendly, thorough and accurate service. For Physical Evidence, the Belangi Syariah Takengon Hotel has a 3-story building, the first floor is filled with an AC lobby, smoking area and mini market and there is an ATM machine, the second and third floors are filled with hotel rooms. In the Process, the Belangi Syariah Takengon Hotel service process collaborates with online hotel booking services, such as tiket.com, booking.com, traveloka.com, pegipegi.com and others, and customers can also come by telephone or come in person, method Payment can be made via cash and non-cash. Finally, for Promotion, there are two strategies implemented at the Belangi Syariah Takengon Hotel, namely pull and push strategies that utilize various social media, placing advertisements in mass media, electronic media, as well as trying to be active in government and non-government activities.